DIGITAL JUSTICE AND THE FUTURE OF CIVIL MEDIATION: A NORMATIVE ANALYSIS OF THE RECOGNITION OF ELECTRONIC MEDIATION AGREEMENTS - Saur Oloan Hamonangan Situngkir; Binsar Jon Vic (MALA IN SE: Jurnal Hukum Pidana, Kriminologi, dan Viktimologi, 2026)
The development of information technology has encouraged the transformation of the justice system towards the concept of digital justice, which utilizes digital technology to improve efficiency, transparency, and access to justice. In the context of civil dispute resolution in Indonesia, this transformation has encouraged the emergence of electronic mediation practices, which are the mediation process carried out through digital media. However, these developments raise legal issues related to the position and legal recognition of mediation agreements made electronically, especially regarding their evidentiary and executory power in the civil procedure law system. This research aims to analyse the concept of digital justice in civil mediation, examine the legal position of electronic mediation agreements in the civil law system, and formulate a model for legal recognition of these agreements in the judicial system. This research uses normative legal research methods with a legislative and conceptual approach through literature studies on relevant laws and regulations, books, and scientific journal articles. The results of the study show that electronic mediation agreements in principle meet the legal requirements of the agreement and can be recognized as legal documents based on the provisions regarding electronic documents, but there is still uncertainty about its executory power. Therefore, a legal recognition model is needed that integrates electronic mediation agreements with the digital justice system through registration, verification, and ratification mechanisms by the courts so that it can obtain the status of an electronic peace deed.